1995
DOI: 10.1164/ajrccm.152.3.7663812
|View full text |Cite
|
Sign up to set email alerts
|

Gender effect on prognosis of patients receiving long-term home oxygen therapy. The Respiratory Failure Research Group in Japan.

Abstract: Although long-term home oxygen therapy (LTOT) certainly prolongs survival, it is not known whether this advantageous effect is similar for both sexes. In this study, we analyzed sex-related differences in survival based on a very large population that had received LTOT from 1986 to 1993. A total of 9,759 patients with chronic obstructive pulmonary disease (COPD), sequelae of tuberculosis (TBsq), and chronic interstitial pneumonia (IP) were selected in 1,212 medical institutions for analysis of survival rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 0 publications
3
40
3
1
Order By: Relevance
“…A Japanese study of patients treated with LTOT for COPD, tuberculosis sequelae, or interstitial pneumonia showed significantly better survival in women, despite a higher average baseline Pa CO 2 (see Figure E1) (52). This finding was confirmed in a meta-analysis of LTOT in which a survival advantage also existed for women (53).…”
Section: Therapeutic Implicationsmentioning
confidence: 78%
“…A Japanese study of patients treated with LTOT for COPD, tuberculosis sequelae, or interstitial pneumonia showed significantly better survival in women, despite a higher average baseline Pa CO 2 (see Figure E1) (52). This finding was confirmed in a meta-analysis of LTOT in which a survival advantage also existed for women (53).…”
Section: Therapeutic Implicationsmentioning
confidence: 78%
“…Gender differences: These differences for COPD survival prognosis have been reported repeatedly but remain controversial 8,[31][32][33] . Some have reported that women have better survival 8,31,32 , but others describe contradictory findings 33 .…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%
“…Some have reported that women have better survival 8,31,32 , but others describe contradictory findings 33 . We hypothesize that it is difficult to adjust all coverable parameters in multiple-variable analysis when comparing both sexes because the two sexes have different FEV 1 predicting formulas and different reference values for exercise tolerance tests.…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%
“…Bu durumun cinsiyetler arasında sigara tüketim oranındaki ve sigaranın olumsuz etkilerine olan duyarlılıktaki farklılıklardan kaynaklanabileceği düşünülmektedir (6). Kadın KOAH hastalarında hastalığın seyrinin daha iyi olduğunu ifade eden çalışma sonuçlarının yanı sıra, (3,7); kadınlarda atak sayısının ve dispne skorlarının daha yüksek, yaşam kalitesi skorlarının daha düşük, (4); hastalık şiddeti (8), hastaneye yatış sıklığı (6) ve mortalite oranlarının (9) daha yüksek olduğunu gösteren çalışma sonuçları da bulunmaktadır.…”
unclassified